Pengaruh Pembelajaran Akidah Akhlak terhadap Perilaku Peserta Didik Kelas X di MAN 1 Kabupaten Bogor - Elawati Fitri; Hasan Basri Tanjung; Andestend Andestend (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
Based on initial observations by the author carried out in class By learning moral beliefs, it is hoped that it will be able to produce students who have noble morals in their daily behavior. The aim of this research is to determine the effect of learning moral beliefs on the behavior of class X IPA MAN 1 Bogor students. The method used in this research is correlation with a quantitative approach with data collection using questionnaires to obtain or collect information regarding the influence of learning moral beliefs on the behavior of class X students at MAN 1 Bogor Regency. Then a simple linear regression test was carried out using SPSS 22 to determine the significant results of the influence of learning moral beliefs on the behavior of class have a significant influence. The calculated T value with a significance level of 0.05% with degrees of freedom (df) = N-2 (62-2) = 60, obtained Tcount = 5.206 > Ttable 1671. Because Tcount > Ttable then Ho is rejected and Ha is accepted which means there is an influence learning moral beliefs on the behavior of class X students at MAN 1 Bogor.